Factors Hindering the Proper Management of Academic Libraries in Kabale Municipality: A Case Study of the Uganda Martyrs University Kabale Campus Library. - Oliva, Arineitwe (Kabale University, 2019)
A Research Report Submitted to the Department of Library and Information Science in Partial Fulfillment of the Requirement of the award of Diploma of Library and Information Science of Kabale University